2016
DOI: 10.1017/s0022215115003473
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the protective effects of intratympanic dexamethasone and methylprednisolone against cisplatin-induced ototoxicity

Abstract: Dexamethasone (and possibly methylprednisolone) may be clinically useful as an intratympanic chemopreventive agent to treat cisplatin ototoxicity. Future clinical studies should investigate the use of dexamethasone for this purpose in adult patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…15,16 However, systemic administration of DEX led to antitumor interference with CDDP due to the downregulation of apoptosis gene. 17 Moreover, intratympanic administration of DEX has yielded conflicting results, owing to the elimination of the drug through the eustachian tube, rapid clearance of drugs, and nonspecific distribution in the inner ear. Nanotechnologies have advantages such as sustained release and specific targeting, which have attracted great attention in the past decades for delivering agents to the inner ear.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 However, systemic administration of DEX led to antitumor interference with CDDP due to the downregulation of apoptosis gene. 17 Moreover, intratympanic administration of DEX has yielded conflicting results, owing to the elimination of the drug through the eustachian tube, rapid clearance of drugs, and nonspecific distribution in the inner ear. Nanotechnologies have advantages such as sustained release and specific targeting, which have attracted great attention in the past decades for delivering agents to the inner ear.…”
Section: Introductionmentioning
confidence: 99%
“…26 This loss typically starts at the first row of OHCs in the basal turn of cochlea, followed by the other OHC rows. 21,26,27 With increasing doses or prolonged administration, it progresses towards more apically located cochlear turns and, eventually, to the single row of inner hair cells. 26 Studies have shown that cisplatin causes an increase in auditory threshold due to the blockade of ion transduction International Journal of Hematology and Oncology channels and degeneration of sensory cells.…”
Section: Discussionmentioning
confidence: 99%
“…In experimental studies 19,21,23 , it was observed that the area damaged in cochlea after cisplatin administration was the organ of Corti accompanied by OHC loss, and even though this damage was more severe in the basal turn, it was observed in all turns of cochlea. Our SEM findings in the cisplatin group showed severe damage in the OHCs at the basal and middle turn of cochlea compared to the control group and the cisplatin/steroid group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations